Saliva testing after single and chronic administration of dihydrocodeine - Skopp, Gisela; Pötsch-Schneider, Lucia Edeltraud; Klinder, Klaus; Richter, Barbara; Aderjan, Rolf; Mattern, Rainer (International journal of legal medicine, 2001)
In the present study, concentrations of dihydrocodeine and its metabolites in saliva and serum were compared after single low-dose and chronic high-dosage administration of the drug. In the first investigation, blood and saliva were collected periodically from six subjects after oral administration of 60 mg dihydrocodeine. In the second study, 20 subjects on oral dihydrocodeine maintenance provided single samples of blood and saliva simultaneously. Serum protein binding of salivary analytes and their recovery from the adsorbing material of the collection device as well as pH values of saliva samples were determined. The fluids were analyzed for dihydrocodeine and the major metabolites by high-performance liquid chromatography. In the single dose study dihydrocodeine was the only analyte found in saliva for up to 12-24 h post-dose. The half-life of dihydrocodeine in saliva was about twice that found in blood. The ratios of saliva/ serum concentrations ranged from 1.2 to 17.0. After chronic high-dosage use, dihydrocodeine was the main salivary analyte and N-nordihydrocodeine was present in a few samples. Saliva/serum concentration ratios of dihydrocodeine were strongly dependent on the pH value of saliva and, to a lesser extent, on serum-protein binding. The saliva/ serum ratios were more similar after chronic administration. The data suggest a passive diffusion process as the underlying mechanism for the transport of dihydrocodeine into saliva. After both single and chronic use, the presence of the drug in saliva can be used as evidence of recent substance administration.
Gesehen am 27.04.2021